Safety evaluation of seabuckthorn (Hippophae rhamnoides) leaves in Japanese quail - Vikram Patial (Veterinary World, 2013)
Aim: The present study was designed to evaluate the safety of seabuckthorn (Hippophae rhamnoides L. Elaeagnaceae) leaves added in the diet of Japanese quail. Materials and Methods: A total of ninety quail chicks were randomly divided into 2 groups and fed a standard quail chick mash added with or without 2% SBT leaf powder (Group SX), and a standard quail chick mash (Group CX, control) for 21 days. Six animals from each group were randomly sacrificed at 7, 14 and 21 day post feeding. Blood and tissue samples were collected for biochemical and histopathological studies.Results: The inclusion of SBT in quail diet did not affect the weekly body weights, clinical signs or mortality among the birds. The serum biochemical parameters like alanine transaminase, total protein, albumin, cholesterol and uric acid values in SBT treated group were found at par with those in the control group. Gross and histopathological studies of various internal organs such as liver, kidneys, heart, spleen, proventriculus, small intestine, bursa and thymus did not reveal any significant lesions in the tissue sections. However, proliferation of lymphoid tissue was a prominent finding noted in different lymphoid organs.Conclusion: In conclusion, the addition of seabuckthorn leaf powder at 2% level in the diet of Japanese quail was found to be safe and it can be used as a feed additive.